Labour Law No. 12/2003 = قانون العمل رقم 12 لسنة 2003. (2025)
1. Definitions and General provisions -- 2. Individual Labor Relationships -- 3. Vocational Guidance and Training -- 4. Collective Labor Relationships -- 5. Vocational Safety and Health and Ensuring Labor Environment Security -- 6. Inspection on Work, Judicial Police Authority and Penalties